2023
DOI: 10.1093/jnci/djad028
|View full text |Cite
|
Sign up to set email alerts
|

Test performance metrics for breast, cervical, colon, and lung cancer screening: a systematic review

Abstract: Background Multiple quality metrics have been recommended to ensure consistent, high-quality execution of screening tests for breast, cervical, colorectal and lung cancers. However, minimal data exist evaluating the evidence base supporting these recommendations and the consistency of definitions and concepts included within and between cancer types. Methods We performed a systematic review for each cancer type using MEDLINE,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The existing literature does not yet provide a target accuracy for classifying images related to cervical cancer screening. In [ 34 ], the authors concluded that guidelines from screening programs and professional organizations lack cited evidence supporting the performance metrics for cervical cancer tests. For example, the United Kingdom’s Office for Health Improvement & Disparities [ 35 ] set a performance threshold of a sensitivity greater than 90% for all abnormalities and a sensitivity greater than 95% for high-grade abnormalities, based on the accuracy of the initial cytology examination as determined by rapid review.…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The existing literature does not yet provide a target accuracy for classifying images related to cervical cancer screening. In [ 34 ], the authors concluded that guidelines from screening programs and professional organizations lack cited evidence supporting the performance metrics for cervical cancer tests. For example, the United Kingdom’s Office for Health Improvement & Disparities [ 35 ] set a performance threshold of a sensitivity greater than 90% for all abnormalities and a sensitivity greater than 95% for high-grade abnormalities, based on the accuracy of the initial cytology examination as determined by rapid review.…”
Section: Analysis and Discussionmentioning
confidence: 99%